AKTIVITAS ANTIOKSIDAN DAN ANTIBAKTERI EKSTRAK POLAR DAN NON POLAR BIJI SELASIH (Ocimum sanctum Linn) [Antioxidant and Antibacterial Activities from Polar and Non Polar Basil (Ocimum sanctum Linn) Seed Extracts] - Agustina D. R. Nurcahyanti; Lusiawati - Dewi; Kris H. Timotius (Jurnal Teknologi dan Industri Pangan, 2011)
The aims of this study were to determine total phenolic content, antioxidant activity and antibacterial activity of polar and nonpolar extracts of basil (O. sanctum L.) seed. Seeds of basil (O. sanctum L.) were extracted using a soxhlet extractor using four types organic solvent, i.e. chloroform, ethyl acetate, acetone, and methanol for eight hours each. The total phenolic content was determined using Folin Ciocalteu method, antioxidant activity was determined using reducing power and DPPH (1,1-diphenyl,2-picrylhydrazyl) scavenging activity methods, while antibacterial activity was tested using agar diffusion method. The result showed that the highest total phenolic content and antioxidant activity was obtained in methanol extract with 3.63 ± 0.21 mgGAE/g phenolic total, 58.39 ± 3.81 mek/g using reducing power method and 85.73 ± 0.86% free radical scavenging activity. Furthermore the result of antibacterial activity testing showed that the highest diameter of inhibition zone was observed in ethyl acetate extract inhibition on E.coli, P.aeruginosa, B.subtilis, and S.aureus where its inhibition zone were 13.53 ± 0.63; 10.67 ± 1.05; 14.93 ± 0.80, and 13.46 ± 0.79 mm, respectively. This result suggests that both polar and nonpolar basil seed extracts possess specific biological activity. This data provide valuable and strong database for exploration of natural antibacterial agents and antioxidant for food and health industry application.